Long-term survival of subglottic adenoid cystic carcinoma: a case report - Yin, Yu-Ting; Gui, Chao (Frontiers in Oncology, 2025)
Adenoid cystic carcinoma of the larynx is rare, mainly localizing in the subglottic region. The clinical presentation is predominantly characterized by dyspnea and hoarseness. In this study, a 38-year-old woman presented symptoms that included hoarseness, wheezing, and coughing. A diagnosis of subglottic adenoid cystic carcinoma was made by laryngoscopy and biopsy and a total laryngectomy was subsequently performed. A decade after the initial surgical intervention, the tumor recurred in the local region. Consequently, a subsequent surgical procedure was undertaken, accompanied by postoperative radiotherapy. A subsequent 5-year follow-up examination revealed no evidence of local recurrence or distant metastasis. Subglottic adenoid cystic carcinoma is an uncommon malignancy. A comprehensive surgical excision can yield a favorable therapeutic outcome. In cases of recurrence, subsequent surgical intervention and postoperative supplemental radiotherapy can achieve positive results.